PELAKSANAAN KHITANAN (SIRKUMSISI) MASSAL GRATIS DALAM RANGKA MERAYAKAN DUA DEKADE RSI SITI RAHMAH PADANG - Mhd Nurhuda; Siana, Yusti; Dian Puspita (Yayasan Nusantara Hasana Berdikari, 2024)
Circumcision or circumcision in men is one of the interventions that can be done to reduce the incidence of Human Immunodeficiency Virus (HIV). This action is a minor surgical procedure by removing part or all of the foreskin (prepuce) to maintain penis hygiene. Globally and over the past 10 years have shown that circumcision activities have a substantial effect on independent prevention of HIV. In the framework of RSI's Siti rahmah two-decade anniversary, community service was carried out in the form of free mass circumcision activities involving competent doctors and medical personnel who can provide benefits to the community. This community service activity is an integral part of the Tri Dharma of Higher Education. This activity was carried out at RSI Siti Rahmah on June 29, 2024. Before circumcision, screening was carried out to eliminate patients with contraindications such as buried penis and hypospadias. The achievements of the implementation of the Circumcision activity with a total of 51 participants and 3 people had contraindications. The activity went smoothly. The parents of the mass circumcision participants were given education in post-circumcision wound care so that wound healing would be perfect.